2012
DOI: 10.1200/jco.2011.38.5740
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Gene Expression Profile Testing and Association With Use of Chemotherapy Among Women With Breast Cancer

Abstract: A B S T R A C T PurposeGene expression profile (GEP) testing is a relatively new technology that offers the potential of personalized medicine to patients, yet little is known about its adoption into routine practice. One of the first commercially available GEP tests, a 21-gene profile, was developed to estimate the benefit of adjuvant chemotherapy for hormone receptor-positive breast cancer (HR-positive BC). Patients and MethodsBy using a prospective registry data set outlining the routine care provided to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 33 publications
(6 reference statements)
8
112
2
1
Order By: Relevance
“…The test is now in use in many clinical centers. 2,3 However, until definitive evidence for clinical utility is available, clinicians must decide on a case-by-case basis whether to offer the test to individual patients.…”
Section: Considerations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The test is now in use in many clinical centers. 2,3 However, until definitive evidence for clinical utility is available, clinicians must decide on a case-by-case basis whether to offer the test to individual patients.…”
Section: Considerations For Practicementioning
confidence: 99%
“…A survey of the care of 7,375 women treated at 11 comprehensive cancer centers and six community-based cancer centers in the United States found an overall decrease in chemotherapy use from 53.9 to 47.0% (P < 0.001). 3 A survey of 6,229 patients registered on an electronic health record database found an association between RS and chemotherapy use (P < 0.001). 34 • In these surveys, approximately 37% of patients were in the intermediate-risk category, for whom chemotherapy benefit is uncertain, compared with 22% in the initial studies by Paik et al 3,23,34 The prospective TAILORx trial 35,36 focuses on the intermediate-risk group, but the trial is not scheduled for completion until 2017.…”
mentioning
confidence: 99%
“…Although the results of health technology assessments raise questions about the clinical utility of the 21-gene expression assay, medical oncologists are using test results in clinical practice to help inform decision-making with respect to patients who can safely avoid adjuvant chemotherapy [10][11][12] . The short-and long-term risks of adjuvant chemotherapy have been well documented, and there are concerns about the overtreatment of patients having breast cancer with low-risk features 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area can yield valuable information about how oncologists use new technologies in less-controlled, non-research settings. For example, Hassett et al 11 used a prospective registry that collected data from 17 comprehensive and community cancer centres to assess gep test adoption for women diagnosed with breast cancer between 2006 and 2008. They found that gep testing increased over time, with an overall reduction in use of adjuvant chemotherapy in hormone receptorpositive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation